Modelling passengers' activity choice in airport terminal before the security checkpoint: the case of portela airport in Lisbon - Kalakou, S.; Moura, F. (Transportation Research Procedia, 2015)
Airports are transport facilities that accommodate both processes related to the passenger air-trip and usually many non-aeronautical activities. This paper aims to explain and predict passenger activity choices at the airport terminal area before the security control. Lisbon Portela airport was used as a case study and pertinent data was collected at the airport by the authors. A multinomial Logit model was estimated to explain passengers' choices regarding activities in the terminal and more specifically, whether passengers choose to perform only aeronautical activities before the security checkpoint or they choose both aeronautical and non-aeronautical activities. Aspects such as travel frequency, travelling for business, performing the check-in online and having planned the activities before arriving at the airport influence the passengers towards not performing discretionary activities before security. Passengers travelling to international destinations while not living in the city of the airport and passengers arriving at the airport accompanied by friends or relatives were more likely to use the non-aeronautical areas. When testing an increase in the proportion of the passengers who complete the check-in online from 30% to 70%, we found that the share of the passengers who perform only aeronautical activities would increase from 47% to 53%. This modelling approach can be used when analyzing scenarios of the airport's operations in the future considering changes in passengers' behavior.